Rheumatoid arthritis and hypothyroidism: a bidirectional Mendelian randomization study - Duan, Lincheng; Chen, Dongqing; Shi, Yue; Ye, Senlin; Dou, Shulin; Feng, Yue (Frontiers in Immunology, 2023)
Object: Though significant correlations between rheumatoid arthritis (RA) and hypothyroidism have been found in earlier observational studies, their underlying causal relationship is still unknown.Mendelian randomization (MR) was used in the current study to assess the bidirectional causation between RA and hypothyroidism.We gathered summary data from genome-wide association studies (GWASs) of RA and hypothyroidism in people of European descent. Then, using data from the FinnGen consortium, we replicated our findings. Three approaches were employed to assess the causal link between RA and hypothyroidism: MR-Egger, weighted median (WM), and inverse variance weighted (IVW). The pleiotropy and heterogeneity were examined using a variety of techniques, including the MR-Egger intercept, the MR-PRESSO approach, the leave-one-out method, and the Cochran's Q test.The study looked at a bidirectional incidental relationship between RA and hypothyroidism.The risk of hypothyroidism increased with RA (IVW odds ratio (OR) = 1.28, 95% confidence interval (CI) = 1.18-1.39, P = 8.30E-10), as did the risk of secondary hypothyroidism (IVW OR = 1.12, 95% CI = 1.05-1.21, P = 9.64E-4). The results of reverse MR analysis revealed that hypothyroidism (IVW OR = 1.68, 95% CI = 1.51-1.88, P = 4.87E-21) and secondary hypothyroidism (IVW OR = 1.74, 95% CI = 1.50-2.01, P = 1.91E-13) were linked to an increased risk of RA. Additionally, we obtain the same results in the duplicated datasets as well, which makes our results even more reliable. This study revealed no evidence of horizontal pleiotropy.The present study established a bidirectional causal link between RA and hypothyroidism. However, it differs slightly from the findings of prior observational studies, suggesting that future research should concentrate on the interaction mechanisms between RA and hypothyroidism.